A need analysis for a communicative English mobile learning module for healthcare professionals / Nawal Mustafa, Norazah Mohd Nordin and Mohamed Amin Embi - Mustafa, Nawal; Mohd Nordin, Norazah; Embi, Mohd Amin (UiTM Press, 2017)
The ability to communicate efficiently in English is a highly sought after skill for healthcare professionals. Training for this skill is usually done in a traditional classroom setting and requires time and a venue to be allocated for the learners to participate in the training sessions. Working adults in the healthcare industry find this a constraint due to their hectic scheduling in the hospital. This study aims to identify the most suitable content for an English language communication course that caters to the specific language functions in the hospital, and to determine the feasibility of offering the course on a mobile platform. A total of 38 questionnaires were administered and a focus group discussion was conducted with 5 representatives of each healthcare profession in a private hospital namely nurses, radiographers, physiotherapists, pharmacists and hospital administrators. Descriptive statistics were used to analyse the survey data and a thematic analysis was performed to derive the themes emerging from the interview. The results demonstrated that the adult learners were able to identify their preferred content based on their own work experiences. Moreover, the preference of using a mobile device for a language course appealed to them.